After integration: Islam, conviviality and contentious politics in Europe - Burchardt, Marian; Michalowski, Ines (Springer VS, 2015)
Part I. Theoretical Perspectives and Cross-National Comparison -- After Integration : Islam, Conviviality and Contentious Politics in Europe / Marian Burchardt and Ines Michalowski -- Figurational Change and Primordialism in a Multicultural Society : A Model Explained on the Basis of the German Case / Jörg Hüttermann -- Incorporating Muslim Migrants in Western Nation States : A Comparison of the United Kingdom, France, and Germany / Matthias Koenig -- Muslim Mobilization Between Self-Organization, State-Recognized Consultative Bodies and Political Participation / Jonathan Laurence -- Institutional Change and the Incorporation of Muslim Populations : Religious Freedoms, Equality and Cultural Diversity / Marcel Maussen -- Islam in Europe : Cross-National Differences in Accommodation and Explanations / Ines Michalowski and Marian Burchardt -- Part II. Islam in Selected European Countries -- Islam and Muslims in Austria / Astrid Mattes and Sieglinde Rosenberger -- Islam in Belgium : From Formal Recognition to Public Contestation / Corinne Torrekens -- Islam and Muslims in Denmark / Brian Arly Jacobsen -- Islam and Laïcité in France / Leyla Arslan -- Islam and Dutch Contestations Over Secularity / Cora Schuh -- Islam in Contemporary Portugal / Luís Pais Bernardo -- Governing Religious Diversity Amid National Redefinition : Muslim Incorporation in Spain / Avi Astor -- Islam in Sweden : Institutionalization, Public Debates and Discursive Paradoxes / Johan Cato -- How Foreigners Became Muslims : Switzerland's Path to Accommodating Islam as a New Religion / Gianni D'Amato -- Muslims in the UK / Paul Weller and Sariya Cheruvallil-Contractor
Literaturangaben
Keywords: Aufsatzsammlung; Integration; Islam; Europa